HUBUNGAN TINGKAT STRES DENGAN MEKANISME KOPING PADA LANSIA YANG MENDERITA DIABETES MELITUS DI DESA SANJA CITEUREUP BOGOR - Rustiani Ayu Anggraeni (2020)
Diabetes mellitus is a chronic disease due to metabolic disorders that cause instability in blood sugar levels. Psychosocial factors that occur due to instability of blood sugar levels are stress. Psychological stress can affect glycemic control. One effective way to deal with stress in patients with diabetes mellitus is by optimizing the adaptive coping mechanism. This study aims to determine the relationship of stress levels with coping mechanisms in the elderly who suffer from diabetes mellitus in the Village of Sanja Citeureup Bogor. The design of this study was analyzed quantitatively using descriptive analytic tectics with aapproach cross sectional. Thetechnique samplingtotal sampling a total of 32 respondents. The analysis used in the univariate is the proportion test and the analysis used in the bivariate is chi square. The results of this study indicate there is a relationship between stress levels and coping mechanisms in the elderly who suffer from diabetes mellitus with a pvalue of 0.005 ≤ 0.05. It is expected that the client of diabetes mellitus while maintaining a healthy lifestyle such as maintaining a healthy diet, sufficient activity, good sres management, and being able to have an adaptive coping mechanism.